Is dermoscopy useful in pediatric dermatology? - Bonifazi, E.; Milano, A. (European Journal of Pediatric Dermatology, 2004)
Dermoscopy is mainly used in the diagnosis of melanoma. As the latter and other pigmented lesions, such as seborrheic keratoses and basal cell carcinoma, are almost inexistent in childhood, one could conclude that dermoscopy is not useful in childhood. All dermatologists know it. However, due to varios reasons, mainly dermatologists using dermoscopy in adults started to use the dermoscope also in children. As congenital melanocytic nevus is indicated as possible precursor of melanoma, few reports concerning these nevi started to appear in the dermatological literature. Some of these reports exclusively regard congenital nevi (3, 5, 9, 10, 11), whereas other reports include data on these nevi among those ones regarding other nevi (2, 6, 7)...